2008
DOI: 10.1177/1066480708323203
|View full text |Cite
|
Sign up to set email alerts
|

Spousal Disclosure of Extramarital Relationships: Attitudes of Marriage and Family Therapists

Abstract: This article presents attitudes of clinical members of the American Association of Marriage and Family Therapists (N = 332) toward spousal disclosure of extramarital relationships. A survey was developed in which an affair was defined as a sexual and emotional secretive relationship occurring concurrent to a committed, cohabiting relationship. Therapist demographic variables that were found to have a significant relationship with attitudes toward affair disclosure were age and level of graduate degree. A large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 12 publications
2
21
0
1
Order By: Relevance
“…Though this speaks to dearth of published research on the subject, it also speaks to the training of the couple’s counselor. Moreover, a recent survey of 1,000 members of the AAMFT reported that 74% of the respondents disagreed that they received adequate training regarding treatment of extramarital affairs (Softas-Nall, Beadle, Newell, & Helm, 2008).…”
Section: Addressing Extramarital Affairs In Counselingmentioning
confidence: 99%
See 4 more Smart Citations
“…Though this speaks to dearth of published research on the subject, it also speaks to the training of the couple’s counselor. Moreover, a recent survey of 1,000 members of the AAMFT reported that 74% of the respondents disagreed that they received adequate training regarding treatment of extramarital affairs (Softas-Nall, Beadle, Newell, & Helm, 2008).…”
Section: Addressing Extramarital Affairs In Counselingmentioning
confidence: 99%
“…Because of potential negative consequences associated with disclosure, counselors disagree as to how much information should be brought back to the couple and how much information should remain secret (Softas-Nall, et al, 2008; Weiner & Starr, 1989); however, experts in the field have advised partners to disclose any extramarital affair (Softas-Nall et al, 2008). It is believed that ongoing extramarital affairs undermine the clinician and their ability to conduct couples counseling and thereby need to be stopped and disclosed to their partner (Whisman & Wagers, 2005).…”
Section: The Process Of Disclosurementioning
confidence: 99%
See 3 more Smart Citations